The Role of the Vice Principal for Public Relations in Improving the School's Reputation - Rozandi Rozandi; Zahrah Usrotussaidah; Sindi Anugrah; Windi Ardiani; Sandi Novaldo; Irwan Fathurrochman (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2026)
This study aims to analyze the strategic role of the Deputy Principal for Public Relations in enhancing the reputation of SMA Negeri 3 Rejang Lebong. The study uses a descriptive qualitative approach with a case study design through interviews, observations, and document analysis. The focus of the study is how public relations functions are carried out strategically in building public image and trust. The findings show that public relations plays a role not only as a conveyor of information, but also as a managerial actor involved in communication planning, strengthening the school's positioning, and proactive issue management. The strategies applied integrate two-way communication with the principles of educational marketing management through digital and conventional promotion, publication of achievements, and external collaboration. The contribution of this research lies in the identification of a strategic-integrative public relations model that places reputation management as a key managerial function in enhancing public trust and school competitiveness.